Seroprevalence of Sarcocystis falcatula in Two Islands of Malaysia using Recombinant Surface Antigen 4 - Nadzirah, Tengku-Idris Tengku Idzzan (Korean J Parasitol, 2020)
Sarcocystosis was diagnosed worldwide by serodiagnostic tests utilising the whole parasite, for which the protozoa were maintained in vitro are more costly. In this study, antigenicity of Sarcocystis falcatula recombinant protein (rSfSAG4) was investigated towards the local communities of Pangkor and Tioman Islands and its seroprevalence was surveyed in these islands. A total of 348 human sera were tested using rSfSAG4 by Western blot and ELISA. High prevalence of sarcocystosis was observed in Tioman Island (80.6%) than in Pangkor Island (50.0%) by Western blot. In ELISA, the seroprevalence observed in Tioman Island was 45.9%, whereas in Pangkor Island 63.0%. In other parasitic infections, the prevalence was 34.0% by Western blot and 46.0% by ELISA. In healthy control group, 7% by Western blot and 8% by ELISA showed positivity to rSfSAG4. It is suggested SfSAG4 is a candidate antigen to measure seroprevalence of sarcocystosis.